Business Communication Adaptation of Micro, Small, and Medium Enterprises (MSMEs) in the Transition from Offline Sales Systems to Digital Marketplaces - Elsaday Sihombing; Zehroh Zehroh; Rio Kurniawan (Literasi Nusantara, 2026)
The development of digital technology has brought changes in various fields, including the business sector. These changes encourage many Micro, Small, and Medium Enterprises (MSMEs) to shift from offline sales systems to digital marketplaces. This transition not only changes the way businesses sell their products but also affects the pattern of communication with consumers. This study aims to examine the adaptation process of business communication among MSMEs during the transition from offline to digital marketplaces, the changes in communication patterns, and the supporting and inhibiting factors in the process. This research employed a qualitative method with a descriptive approach. Data were collected through interviews, observations, and documentation. The results show that MSMEs have shifted their communication patterns from face-to-face interactions to digital communication through chat features, product descriptions, and customer reviews. Fast responses and communicative language also play an important role in building consumer trust. However, several obstacles are still encountered, such as low digital literacy and limited ability to manage digital communication. Therefore, the ability to adapt business communication becomes an important factor in improving the competitiveness of MSMEs in the digital era.